A very rare case of a newborn with tetrasomy 9p and literature review - Süleyman, Merve; Oğuz, Sümeyra; Kaykı, Gözdem; Çelik, Hasan Tolga; Şimsek-Kiper, Pelin Özlem; Utine, Gülen Eda; Yiğit, Şule (The Turkish Journal of Pediatrics, 2022)
Background. Tetrasomy 9p is a rare genetic condition which usually results from a supernumerary isochromosome derived from the short arm of chromosome 9. Phenotypic findings include multiple congenital anomalies, facial dysmorphism, growth and developmental delays, and also vary according to the presence and degree of mosaicism. Case. We report on a newborn with tetrasomy 9p who deceased in the newborn period. She had facial features including low-set and anteverted ears, hypertelorism, prominent nasal bridge, and microretrognathia. Bilateral ventriculomegaly, vermian hypoplasia and corpus callosum agenesis were detected on magnetic resonance imaging and double outlet right ventricle (tetralogy of Fallot type), secundum atrial septal defect, and persistent left superior vena cava were displayed by echocardiography. Microarray analysis revealed 38,584 kb tetrasomic region at 9p24.3p13.1. We also present a review of the literature suggesting that there is a recognizable phenotype for this condition and an assessment of cardiac manifestations based on the size and the localization of the breakpoints. Conclusions. We conclude that cardiac manifestations do not differ according to the localization of the breakpoint. Persistent left superior vena cava seems to be consistent with breakpoints distal to q12, but the present case is different from them by breakpoint p13.1.